PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN KEPRIBADIAN PESERTA DIDIK DI SMP AL- ISLAM BENTENG TELLUE KEC. AMALI KABUPATEN BONE - Hasna, Hasna; Nursyirwan, Nursyirwan; Sulaeman, Sulaeman (JURNAL AL-QAYYIMAH, 2021)
This paper examines the Role of Islamic Religious Education Teachers in Personality Development of Students at SMP Al-Islam Benteng Tellue, Kec. Amali, Bone Regency. Aims to determine the shape of the role of PAI teachers in Personality Development of Students at Al-Islam Middle School Benteng Tellue, Kec. Amali, Bone Regency. This research belongs to the type of field research using a qualitative approach. Data collection was carried out using several instruments including; interview guide, observation guide and related document search using documentation tools. The results showed that the form of the role of PAI teachers in the development of the personality of students at Al-Islam Middle School Benteng Tellue, Kec. Amali Bone Regency can be measured from the behavior patterns shown by students, which include; Discipline, Politeness, and Neatness.